A Dynamic Approach to Combine Components and Aspects - Fernandes, Fabrício de Alexandria; Batista, Thais (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2004: Anais do XVIII Simpósio Brasileiro de Engenharia de Software, 2004)
In this paper we discuss the use of a dynamic approach to combine components and aspects in order to form a CORBA-based application. We use AspectLua, an extension of an interpreted and dynamically typed language – Lua, which supports aspect-oriented programming. We describe the use of AspectLua in the context of a CORBA-based environment. AspectLua explores the reflexive features of Lua and the powerful of its small syntax and allows the dynamic definition of aspects and it also offers support for dynamic weaving. The difference of AspectLua to the traditional aspect-oriented languages is the fact of being interpreted and dynamically typed – this allows the insertion/removal of components and aspects in an application at runtime.